Forensic analysis of arsenic poisoning in Japan by synchrotron radiation X‐ray fluorescence. (30th May 2013) - Kawai, Jun
<x xml:space="preserve">Abstract</x> Synchrotron radiation X‐ray fluorescence (SR‐XRF) analysis reports of a poisoning case by arsenic, 25 July 1998, Japan, for forensic investigation purposes are reviewed. In these forensic analyses, SPring‐8 and KEK‐PF beamlines were used for minor element (Sn, Sb, Mo, Bi, Ba) analysis in the arsenic pesticide specimens, sampled at the crime scene as well as the neighborhood of the suspect. For this case, two kinds of documents were submitted to court: one was a qualitative analysis and said to be a 'pattern recognition' by Prof. Nakai, and the other was, by Profs Taniguchi and Hayakawa, a quantitative analysis after background subtraction, normalized by the sample thickness, where calibration curves were made with reference to the inductively coupled plasma atomic emission spectrometry (ICP‐AES) analysis for reference samples. The final decision of the court was a death sentence based on the qualitative 'pattern recognition'. The present review concludes that the quantitative analysis by Profs Taniguchi and Hayakawa was scientifically more important than the 'pattern recognition' qualitative analysis, because the Taniguchi‐Hayakawa report used novel but reliable data processing methods. The Sn, Sb, and Mo Kα intensities were normalized with respect to the As (major element) Kα (10.5 keV) intensity as a thick target, whereas the Bi and Ba Kα intensities were normalized by the Rayleigh scattering (for 116 keV incident beam) as a thin target. The Taniguchi‐Hayakawa report was the first quantitative report in high‐energy SR‐XRF analysis. The most important conclusion in the present review is that the ICP‐AES was more reliable over these SR‐XRF analyses, because even the beamline selection was not possible without the knowledge of the impurity elements obtained by the ICP‐AES. Five elements (Se, Sn, Sb, Pb, and Bi) were used in ICP‐AES for identification compared with only three elements (Sn, Sb, and Bi) in SR‐XRF. High blank intensity resulted from using Pb for X‐ray collimator in the beamline. Overlapping of the analytical lines of minor Se and major As prevented the use of Se for identification. Recent analysis of Fe, Zn, Mo, and Ba in Nakai's raw spectra measured in 1998 reveals the arsenic stored in the kitchen of the condemned criminal in the death row was significantly different from that of the paper cup used for poisoning. Copyright © 2013 John Wiley & Sons, Ltd.